Pyroelectric ceramic material and preparation method thereof

By using Al and Mn doping and optimizing preparation processes in pyroelectric ceramic materials, the problems of large loss and low pyroelectric coefficient of existing pyroelectric ceramic materials are solved, and higher pyroelectric performance and stability are achieved, and suitable for infrared detection.

CN119661219AInactive Publication Date: 2025-03-21TIANJIN ZHONGKEXING CERAMICS ELECTRONIC TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411891395.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing pyroelectric ceramic materials have problems such as large losses and low pyroelectric coefficients, and it is necessary to optimize the formulation and preparation process to improve performance.

Method used

The pyroelectric ceramic material with the chemical formula (PbO)·(MnO2) 0.08/3·(Nb2O5) 0.04/3·(Sb2O3) 0.04/3·(ZrO2) 0.874·(TiO2) 0.876+xwt% Al2O3+ywt% MnO2 was prepared.

Benefits of technology

It significantly reduces dielectric loss and improves the pyroelectric coefficient, so that the pyroelectric ceramic materials have better comprehensive performance and stability, meeting the demand of the infrared detection market.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200747090000071
    Figure BDA0005200747090000071
  • Figure BDA0005200747090000081
    Figure BDA0005200747090000081
Patent Text Reader

Abstract

The invention provides a pyroelectric ceramic material and a preparation method thereof, and belongs to the technical field of pyroelectric material preparation, the preparation method comprises the following steps: taking Pb3O4, ZrO2, TiO2, Nb2O5, MnO2, Sb2O3 and Al2O3 as raw materials, adding Zr balls to carry out primary ball milling, then drying and pre-sintering, adding Zr balls into the obtained intermediate material to carry out secondary ball milling, and then successively carrying out granulation, dry pressing molding, sintering, silver coating and polarization to obtain the pyroelectric ceramic material. The pyroelectric ceramic material is prepared. By adjusting the formula and the preparation process of the pyroelectric ceramic material, the performance of the pyroelectric ceramic material is optimized, so that the pyroelectric ceramic material has better comprehensive performance, the performance is more stable, and the requirement of the infrared detection market for the comprehensive performance of the material is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of pyroelectric ceramics, in particular to a pyroelectric ceramic material and a preparation method thereof. Background Art

[0002] In recent years, infrared detection and thermal imaging technology has been rapidly developed and applied in both military and civilian fields. In the military field, infrared technology is widely used in weapon preparation in the fields of infrared guidance, remote sensing, night vision, and reconnaissance; in the civilian field, infrared technology plays an important role in fault diagnosis, product quality monitoring, safety monitoring and protection, etc.

[0003] As the core working element in infrared detection and thermal imaging technology, the existing pyroelectric ceramic materials have disadvantages such as large loss and low pyroelectric coefficient. The main reason is that the original pyroelectric ceramic material formula and preparation process need to be further optimized. Summary of the invention

[0004] In view of the above problems, the present invention provides a pyroelectric ceramic material capable of reducing dielectric loss and improving pyroelectric coefficient and a preparation method thereof.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is:

[0006] A pyroelectric ceramic material, the chemical formula of the pyroelectric material is:

[0007] (PbO)·(MnO2) 0.08 / 3 ·(Nb2O5) 0.04 / 3 ·(Sb2O3) 0.04 / 3 ·(ZrO2) 0.874 ·(TiO2) 0.046 +xwt%Al2O3+ywt%MnO2, x=0.3, y=0.08.

[0008] A method for preparing a pyroelectric ceramic material, the preparation method comprising taking Pb3O4, ZrO2, TiO2, Nb2O5, MnO2, Sb2O3 and Al2O3 as raw materials, adding Zr balls for the first ball milling, then drying and pre-sintering, adding Zr balls to the obtained intermediate material for the second ball milling, and then sequentially granulating, dry pressing, sintering, silvering and polarization to obtain the pyroelectric ceramic material.

[0009] Furthermore, the weight ratio of Pb3O4, ZrO2, TiO2, Nb2O5, MnO2, Sb2O3 and Al2O3 is 68.0721~68.0725: 31.2785~31.2788: 1.0674~1.0677: 1.0290~1.0293: 0.6731~0.6734: 1.1284~1.1286; 0.3097~0.3098.

[0010] Furthermore, the preparation method comprises the following steps:

[0011] S1. First ball milling

[0012] Pb3O4, ZrO2, TiO2, Nb2O5, MnO2, Sb2O3 and Al2O3 are mixed as ingredients;

[0013] Add Zr balls, ingredients and deionized water in sequence for the first ball milling;

[0014] S2. Drying

[0015] After the ball milling is completed, the ground material is dried for the first time to obtain the dried material;

[0016] S3, pre-burning

[0017] Pre-burn the dried material to obtain the intermediate material;

[0018] S4, second ball milling

[0019] Add Zr balls, intermediate materials and deionized water in sequence for the second ball milling. After the second ball milling is completed, dry the second ground materials for the second time to obtain the second dried materials.

[0020] S5, Granulation

[0021] The second dried material is sieved, and then polyvinyl alcohol (PVA) is added to perform manual granulation;

[0022] S6, dry pressing

[0023] After the granulation, the material was pressurized to 8MPa for 10s;

[0024] S7, Sintering

[0025] Sintering the pressure-treated material to obtain a sintered material;

[0026] S8, Silver

[0027] The sintered material was silvered by hand brushing to obtain pyroelectric ceramic samples;

[0028] S9, Polarization

[0029] The pyroelectric ceramic sample is polarized by using silicone oil polarization, and after the polarization is completed, the pyroelectric ceramic material is obtained.

[0030] Furthermore, in step S3, the pre-burning temperature is as follows:

[0031] First, the temperature was raised from room temperature to 100°C for the first time, and the time taken for the first heating was 88 to 92 minutes;

[0032] Then, after heating from 100°C to 900°C, the second heating time is 390-410 minutes, and the temperature is maintained at 900°C for 140-160 minutes, and then naturally cooled to obtain the intermediate material.

[0033] Furthermore, in step S7, the sintering temperature is as follows:

[0034] First, the temperature is raised from room temperature to 550°C for the first time, the time of the first heating is 440-460 minutes, and the temperature is maintained at 550°C for 2.95-3.05 hours;

[0035] Then, the temperature is raised from 550°C to 1200°C for a second time, the second heating time is 490-510 minutes, and the temperature is maintained at 1200°C for 4.95-5.05 hours. Finally, the material is naturally cooled to obtain the sintered material.

[0036] Further, in step S1, the weight ratio of Zr balls, ingredients and deionized water is 2:1:0.9-1.1;

[0037] The first ball milling process is performed at a speed of 430-480 r / min and a time of 2.5-3.5 h.

[0038] In step S3, the weight ratio of Zr balls, intermediate material and deionized water is 2:1:0.5-0.7;

[0039] The ball mill speed for the second ball milling is 390-410 r / min and the time is 3.5-4.5 h.

[0040] Furthermore, in step S5, the amount of polyvinyl alcohol added is 5.8-6.2% of the mass ratio of the material obtained after the second drying material is sieved.

[0041] Furthermore, in step S6, the pressurization pressure is 7.8 to 8.2 MPa and the time is 9 to 11 s.

[0042] Furthermore, in step S9, the polarization voltage is 3.4-3.6 KV / mm, the polarization time is 18-22 min, and the polarization temperature is 108-112°C.

[0043] The beneficial effects of the pyroelectric ceramic material and the preparation method thereof of the present invention are:

[0044] The present invention adopts the co-doping of Al and Mn elements to facilitate the growth of grains, so that the uniformity and density of the ceramic sample are improved; at the same time, appropriately increasing the doping amount of MnO2 is helpful to improve the dielectric and pyroelectric properties of the ceramic sample, but excessive doping of MnO2 will cause the deterioration of the dielectric properties of the ceramic sample;

[0045] The present invention optimizes the performance of the pyroelectric ceramic material by adjusting the formula and preparation process of the pyroelectric ceramic material, so that the pyroelectric ceramic material has better comprehensive performance and more stable performance, meeting the comprehensive performance requirements of the infrared detection market for materials;

[0046] The overall process cost of the preparation method of the present invention is low, and the process stability is good mainly by changing the components and the content of the components, the sintering temperature, the holding time and the heating and cooling curve;

[0047] The pyroelectric ceramic material prepared by the present invention has the characteristics of low loss and better material performance. DETAILED DESCRIPTION

[0048] The technical solutions in the embodiments of the present invention are described clearly and completely below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0049] Example 1 A method for preparing a pyroelectric ceramic material

[0050] This embodiment is a method for preparing a pyroelectric ceramic material, which specifically includes the following steps:

[0051] S1. First ball milling

[0052] Pb3O4, ZrO2, TiO2, Nb2O5, MnO2, Sb2O3 and Al2O3 are mixed in a weight ratio of 68.0721:31.2785:1.0674:1.0293:0.6734:1.1284:0.3097 as ingredients;

[0053] Add Zr balls, ingredients and deionized water to the ball mill in sequence for the first ball milling. The weight ratio of Zr balls, ingredients and deionized water is 2:1:1. The speed of the ball mill for the first ball milling is set to 450 r / min. The time for the first ball milling is 3 h.

[0054] S2. Drying

[0055] After the ball milling is completed, the ground material is dried for the first time in an oven at 80°C for 6 hours to obtain a dried material;

[0056] S3, pre-burning

[0057] The dried material is pre-burned, wherein no inert gas is injected during the pre-burning process, and the pre-burning temperature is set according to the following temperature curve:

[0058] First, the temperature was raised from room temperature to 100°C for the first time, and the time taken for the first heating was 90 minutes;

[0059] Then, after heating from 100°C to 900°C, the second heating time is 400 minutes, and the temperature is maintained at 900°C for 150 minutes, and then naturally cooled to obtain the intermediate material.

[0060] S4, second ball milling

[0061] Add Zr balls, intermediate materials and deionized water into the ball mill in sequence for the second ball milling. The weight ratio of Zr balls, intermediate materials and deionized water is 2:1:0.6. Set the ball mill speed to 400 r / min and the ball milling time to 4 h. After the second ball milling, dry the second ground material in an oven at 80°C for 4 h to obtain the second dried material.

[0062] S5. Granulation (artificial granulation)

[0063] The second dried material was passed through a 40-mesh sieve, and then 6% by mass of polyvinyl alcohol (PVA) was added for manual granulation.

[0064] S6, dry pressing

[0065] First, put the granulated material into the mold, then install the mold on the press, and then pressurize to 8MPa for 10s;

[0066] S7, Sintering

[0067] The pressurized material is sintered, and the sintering temperature is set according to the following temperature curve:

[0068] First, the temperature was raised from room temperature to 550°C for 450 min, and then maintained at 550°C for 3 h.

[0069] Then, the temperature is raised from 550°C to 1200°C for a second time. The second heating time is 500 minutes, and the temperature is maintained at 1200°C for 5 hours. Finally, the material is naturally cooled to obtain the sintered material.

[0070] S8, Silver

[0071] The sintered material was silvered by hand brushing to obtain pyroelectric ceramic samples.

[0072] Among them, silvering usually refers to the use of printing to coat the silver paste on the surface of pyroelectric ceramics. This printing method can be screen printing, pad printing, etc. Hand-brushed silvering is a manually operated electrode preparation process. Specifically, it is to use a special silver paste (a paste containing silver powder, binder, solvent and other ingredients), dip the silver paste with a soft brush, and then brush it on the surface of the pyroelectric ceramic body or sintered ceramic. This brushing method is like painting with a brush, applying the silver paste according to the predetermined electrode pattern or coverage area.

[0073] S9, Polarization

[0074] The pyroelectric ceramic sample was polarized by silicone oil polarization, with a polarization voltage of 3.5KV / mm, a polarization time of 20min, and a polarization temperature of 110°C. After the polarization was completed, the pyroelectric ceramic material was obtained, and the chemical formula was (PbO)·(MnO2) 0.08 / 3 ·(Nb2O5) 0.04 / 3 ·(Sb2O3) 0.04 / 3 ·(ZrO2) 0.874 ·(TiO2) 0.046 +xwt%Al2O3+ywt%MnO2, x=0.3, y=0.08, marked as T1.

[0075] Among them, silicone oil polarization is to completely immerse the pyroelectric ceramic sample in a silicone oil container, and then apply a DC electric field to the pyroelectric ceramic sample through electrodes. During the polarization process, the silicone oil always surrounds the ceramic, playing the above-mentioned roles of electric field uniformization, anti-discharge and heat dissipation.

[0076] The performance test of pyroelectric ceramic material T1 showed that the relative dielectric parameter was 194, the dielectric loss tanδ was 0.0004, the piezoelectric coefficient d33 was 59pC / N, the volume resistivity was 3.1GΩ·m, and the pyroelectric coefficient was 3.5×10 -4 C m -2 K -1 , Curie temperature is 190℃.

[0077] Examples 2 to 4 Preparation methods of pyroelectric ceramic materials

[0078] Examples 2 to 4 are respectively methods for preparing pyroelectric ceramic materials. Their steps are basically the same as those of the pyroelectric ceramic material in Example 1, and the only difference is the amount of some raw materials and process parameters. See Table 1 for details:

[0079] Table 1 List of process parameters in Examples 2 to 4

[0080]

[0081]

[0082] The contents of other parts of Examples 2 to 4 are the same as those of Example 1.

[0083] Comparative Examples 1 to 8 Preparation Methods of Pyroelectric Ceramic Materials

[0084] Comparative Examples 1 to 8 are comparative tests of the preparation process of the pyroelectric ceramic material in Example 1, and use the same batch of raw materials and the same process parameters, the only difference is that:

[0085] In Comparative Example 1, only the amount of manganese dioxide was changed, and the proportions of other raw materials and process parameters remained unchanged. The chemical formula of the obtained pyroelectric ceramic material was (PbO·(MnO2) 0.08 / 3 ·(Nb2O5) 0.04 / 3 ·(Sb2O3) 0.04 / 3 ·(ZrO2) 0.874 ·(TiO2) 0.046 +xwt%Al2O3+ywt%MnO2, x=0.3, y=0.04, marked as DT1. The performance test results of the pyroelectric ceramic material DT1 are: relative dielectric parameter is 187, dielectric loss tanδ is 0.001, piezoelectric coefficient d33 is 55pC / N, volume resistivity is 1.8GΩ·m, pyroelectric coefficient is 1.6×10 -4 Cm -2 K -1 , Curie temperature is 180℃.

[0086] In Comparative Example 2, only the amount of manganese dioxide was changed, and the proportions of other raw materials and process parameters remained unchanged. The chemical formula of the obtained pyroelectric ceramic material was (PbO·(MnO2) 0.08 / 3 ·(Nb2O5) 0.04 / 3 ·(Sb2O3) 0.04 / 3 ·(ZrO2) 0.874 ·(TiO2) 0.046 +xwt%Al2O3+ywt%MnO2, x=0.3, y=0.06, marked as DT2. The performance test results of the pyroelectric ceramic material DT1 are as follows: relative dielectric parameter is 193, dielectric loss tanδ is 0.0012, piezoelectric coefficient d33 is 65pC / N, volume resistivity is 1.2GΩ·m, pyroelectric coefficient is 1.1×10 -4 Cm -2 K -1 , Curie temperature is 187.5℃.

[0087] In Comparative Example 3, only the amount of manganese dioxide was changed, and the proportions of other raw materials and process parameters remained unchanged. The chemical formula of the obtained pyroelectric ceramic material was (PbO·(MnO2) 0.08 / 3 ·(Nb2O5) 0.04 / 3 ·(Sb2O3) 0.04 / 3 ·(ZrO2) 0.874 ·(TiO2) 0.046 +xwt%Al2O3+ywt%MnO2, x=0.3, y=0.10, marked as DT3. The performance test results of the pyroelectric ceramic material DT3 are: relative dielectric parameter is 198, dielectric loss tanδ is 0.0015, piezoelectric coefficient d33 is 71pC / N, volume resistivity is 1.0GΩ·m, pyroelectric coefficient is 0.9×10 -4 Cm -2 K -1 , Curie temperature is 170℃.

[0088] In Comparative Example 4, only the amount of manganese dioxide was changed, and the proportions of other raw materials and process parameters remained unchanged. The chemical formula of the obtained pyroelectric ceramic material was (PbO·(MnO2) 0.08 / 3 ·(Nb2O5) 0.04 / 3 ·(Sb2O3) 0.04 / 3 ·(ZrO2) 0.874 ·(TiO2) 0.046 +xwt%Al2O3+ywt%MnO2, x=0.3, y=0.12, marked as DT4. The performance test results of the pyroelectric ceramic material DT4 are as follows: relative dielectric parameter is 199, dielectric loss tanδ is 0.0018, piezoelectric coefficient d33 is 73pC / N, volume resistivity is 0.8GΩ·m, pyroelectric coefficient is 0.5×10 -4 Cm -2 K -1 , Curie temperature is 165℃.

[0089] It can be seen from the comparison between Comparative Examples 1 to 4 and Example 1 that simply changing the amount of manganese dioxide used will lead to a significant decrease in the performance of the pyroelectric ceramic material, wherein the dielectric loss tanδ is significantly increased, and the volume resistivity and the pyroelectric coefficient are significantly reduced, indicating that the pyroelectric material of a specific chemical formula made by a specific ratio of the present invention has lower dielectric loss and higher pyroelectric coefficient.

[0090] In Comparative Example 5, only the amount of aluminum oxide was changed, and the proportions of other raw materials and process parameters remained unchanged. The chemical formula of the obtained pyroelectric ceramic material was (PbO·(MnO2) 0.08 / 3 ·(Nb2O5) 0.04 / 3 ·(Sb2O3) 0.04 / 3 ·(ZrO2)0.874 ·(TiO2) 0.046 +xwt%Al2O3+ywt%MnO2, x=0.296, y=0.08, marked as DT5. The performance test results of the pyroelectric ceramic material DT5 are: relative dielectric parameter is 185, dielectric loss tanδ is 0.002, piezoelectric coefficient d33 is 53pC / N, volume resistivity is 1.7GΩ·m, pyroelectric coefficient is 1.7×10 -4 Cm -2 K -1 , Curie temperature is 182℃.

[0091] In Comparative Example 6, only the amount of aluminum oxide was changed, and the proportions of other raw materials and process parameters remained unchanged. The chemical formula of the obtained pyroelectric ceramic material was (PbO·(MnO2) 0.08 / 3 ·(Nb2O5) 0.04 / 3 ·(Sb2O3) 0.04 / 3 ·(ZrO2) 0.874 ·(TiO2) 0.046 +xwt%Al2O3+ywt%MnO2, x=0.298, y=0.08, marked as DT6. The performance test results of the pyroelectric ceramic material DT6 are: relative dielectric parameter is 191, dielectric loss tanδ is 0.0011, piezoelectric coefficient d33 is 65pC / N, volume resistivity is 1.3GΩ·m, pyroelectric coefficient is 1.2×10 -4 Cm -2 K -1 , Curie temperature is 185℃.

[0092] In Comparative Example 7, only the amount of alumina was changed, and the proportions of other raw materials and process parameters remained unchanged. The chemical formula of the obtained pyroelectric ceramic material was (PbO·(MnO2) 0.08 / 3 ·(Nb2O5) 0.04 / 3 ·(Sb2O3) 0.04 / 3 ·(ZrO2) 0.874 ·(TiO2) 0.046 +xwt%Al2O3+ywt%MnO2, x=0.303, y=0.08, marked as DT7. The performance test results of the pyroelectric ceramic material DT7 are as follows: relative dielectric parameter is 196, dielectric loss tanδ is 0.0016, piezoelectric coefficient d33 is 70pC / N, volume resistivity is 1.2GΩ·m, pyroelectric coefficient is 0.85×10 -4 Cm -2 K -1 , Curie temperature is 172℃.

[0093] In Comparative Example 4, only the amount of aluminum oxide was changed, and the proportions of other raw materials and process parameters remained unchanged. The chemical formula of the obtained pyroelectric ceramic material was (PbO·(MnO2) 0.08 / 3 ·(Nb2O5) 0.04 / 3 ·(Sb2O3) 0.04 / 3 ·(ZrO2) 0.874 ·(TiO2) 0.046 +xwt%Al2O3+ywt%MnO2, x=0.304, y=0.08, marked as DT8. The performance test results of the pyroelectric ceramic material DT8 are: relative dielectric parameter is 198, dielectric loss tanδ is 0.0017, piezoelectric coefficient d33 is 75pC / N, volume resistivity is 0.86GΩ·m, pyroelectric coefficient is 0.53×10 -4 C m -2 K -1 , Curie temperature is 168℃.

[0094] It can be seen from the comparison between Comparative Examples 5 to 8 and Example 1 that simply changing the amount of aluminum oxide used will lead to a significant decrease in the performance of the pyroelectric ceramic material, wherein the dielectric loss tanδ is significantly increased, and the volume resistivity and the pyroelectric coefficient are significantly reduced, indicating that the pyroelectric material of a specific chemical formula made by a specific proportion of the present invention has lower dielectric loss and higher pyroelectric coefficient.

[0095] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A pyroelectric ceramic material, characterized in that: The chemical formula of the pyroelectric material is: (PbO)·(MnO2) 0.08 / 3 ·(Nb2O5) 0.04 / 3 ·(Sb2O3) 0.04 / 3 ·(ZrO2) 0.874 ·(TiO2) 0.046 + xwt%Al2O3+ywt%MnO2, x=0.3, y=0.

08.

2. A method for preparing a pyroelectric ceramic material, characterized in that: The preparation method comprises the following steps: taking Pb3O4, ZrO2, TiO2, Nb2O5, MnO2, Sb2O3 and Al2O3 as raw materials, adding Zr balls for the first ball milling, and then drying and pre-sintering, adding Zr balls to the intermediate material for the second ball milling, and then sequentially granulating, dry pressing, sintering, silvering and polarizing to obtain the pyroelectric ceramic material.

3. The method for preparing a pyroelectric ceramic material according to claim 2, characterized in that: The weight ratio of Pb3O4, ZrO2, TiO2, Nb2O5, MnO2, Sb2O3 and Al2O3 is 68.0721~68.0725: 31.2785~31.2788: 1.0674~1.0677: 1.0290~1.0293: 0.6731~0.6734: 1.1284~1.1286; 0.3097~0.3098.

4. The method for preparing a pyroelectric ceramic material according to claim 2 or 3, characterized in that: The preparation method comprises the following steps: S1. First ball milling Pb3O4, ZrO2, TiO2, Nb2O5, MnO2, Sb2O3 and Al2O3 are mixed as ingredients; Add Zr balls, ingredients and deionized water in sequence for the first ball milling; S2. Drying After the ball milling is completed, the ground material is dried for the first time to obtain the dried material; S3, pre-burning Pre-burn the dried material to obtain the intermediate material; S4, Second ball milling Add Zr balls, intermediate materials and deionized water in sequence for the second ball milling. After the second ball milling is completed, dry the second ground materials for the second time to obtain the second dried materials. S5, Granulation The second dried material is sieved, and then polyvinyl alcohol is added to granulate; S6, dry pressing After the granulation, the material was pressurized to 8MPa for 10s; S7, sintering Sintering the pressure-treated material to obtain a sintered material; S8, Silver The sintered material was silvered by hand brushing to obtain pyroelectric ceramic samples; S9, Polarization The pyroelectric ceramic sample is polarized by using silicone oil polarization, and after the polarization is completed, the pyroelectric ceramic material is obtained.

5. The method for preparing a pyroelectric ceramic material according to claim 4, characterized in that: In step S3, the pre-burning temperature is as follows: First, the temperature was raised from room temperature to 100°C for the first time, and the time taken for the first heating was 88 to 92 minutes; Then, after heating from 100°C to 900°C, the second heating time is 390-410 minutes, and the temperature is maintained at 900°C for 140-160 minutes, and then naturally cooled to obtain the intermediate material.

6. The method for preparing a pyroelectric ceramic material according to claim 4, characterized in that: In step S7, the sintering temperature is as follows: First, the temperature is raised from room temperature to 550°C for the first time, the time of the first heating is 440-460 minutes, and the temperature is maintained at 550°C for 2.95-3.05 hours; Then, the temperature is raised from 550°C to 1200°C for a second time, the second heating time is 490-510 minutes, and the temperature is maintained at 1200°C for 4.95-5.05 hours. Finally, the material is naturally cooled to obtain the sintered material.

7. The method for preparing a pyroelectric ceramic material according to claim 4, characterized in that: In step S1, the weight ratio of Zr balls, ingredients and deionized water is 2:1:0.9-1.1; The first ball milling process is performed at a speed of 430-480 r / min and a time of 2.5-3.5 h. In step S3, the weight ratio of Zr balls, intermediate material and deionized water is 2:1:0.5-0.7; The ball mill speed for the second ball milling is 390-410 r / min and the time is 3.5-4.5 h.

8. The method for preparing a pyroelectric ceramic material according to claim 4, characterized in that: In step S5, the amount of polyvinyl alcohol added is 5.8-6.2% of the mass ratio of the material obtained after the second drying material is sieved.

9. The method for preparing a pyroelectric ceramic material according to claim 4, characterized in that: In step S6, the pressurization pressure is 7.8 to 8.2 MPa and the time is 9 to 11 seconds.

10. The method for preparing a pyroelectric ceramic material according to claim 4, characterized in that: In step S9, the polarization voltage is 3.4-3.6 KV / mm, the polarization time is 18-22 min, and the polarization temperature is 108-112°C.